Design of a Modern Car Parking at the Faculty of Engineering, Technology Applied Design And Fine Art. - Akampurira, Jobathie (Kabale University, 2023)
This report contains several chapters giving an overview of the activities we carried out during the design of modern car parking at Nyabikoni campus. The activities include the following, Introduction of car parking, background, parking areas type, problem statement, Problem statement, Objectives of Project, Main objective, Specific objective, Scope of Project, Scope of Project, Significance, chapter 2: literature review, Related Work, Parking Design Consideration, Needs Analysis, Parking study, Parking Requirement Factor, Physical Requirement, Aesthetics and Safety, chapter 3: methodology, Introduction of Methodology, Design Methodologies, Bench Marking, Data collection, Observation Method, Design using Architecture, Plan Design, Architectural drawings, Arch CAD, Tools Use, Materials, Procedure for Making the Design Model of Car Parking, chapter results and discussion, chapter 5: conclusion, recommendations and skilled acquired, Skills acquired,Challenges faced during the project plan design, Recommendations, Conclusion, References, Pavement design for concrete parking lots. The architecture of parking,